HUBUNGAN POLIMORFISME MTHFR c.677C>T DENGAN FUNGSI KOGNITIF PADA PASIEN STROKE ISKEMIK AKUT DI RSUP DR. SARDJITO - Haq, Arinal; Gofir, Abdul; Ar Rochmah, Mawaddah; Amelia Nur Vidyanti; Yogik Onky Silvana Wijaya, Yogik Onky Silvana Wijaya (PERDOSNI, 2024)
Introduction: Ischemic stroke is an acute cerebrovascular event with cognitive impairment presents as its prevalent manifestation and complication. Methylenetetrahydrofolate reductase (MTHFR) is an important enzyme in folate metabolism through an integral process of cellular metabolism in DNA, RNA and protein methylation. MTHFR c.677C>T polymorphism is considered an important genetic risk factor for stroke and cognitive dysfunction in some populations. Aim: This study aimed to investigate the association between the MTHFR c.677C>T polymorphism and cognitive function in acute ischemic stroke patients in Dr. Sardjito General Hospital Yogyakarta. Methods: We performed a cross-sectional study in 42 consecutive acute ischemic stroke patients. PCR R-FLP was used to examine MTHFR c.677C>T polymorphism. Cognitive function was determined using MoCA-Ina within 24 hours of each patient’s admission, with score 24 is the cut off for cognitive impairment. Results: Of 42 patients, 12 patients (28.6%) showed MTHFR c.677C>T variant. There were 3 patients (25%) with homozygous variant of MTHFR c.677C>T. Cognitive dysfunction was found in 7 patients (16.7%) with MTHFR c.677C>T variant and 18 patients (42.9%) with wild type MTHFR. However, no significant association was found between MTHFR c.677C>T with cognitive function in acute ischemic stroke patients (p=0.921). Discussion: The frequency of MTHFR c.677C>T polymorphism in this study was 28.6% with a quarter of them showing homozygous variant. There was no association between MTHFR c.677C>T polymorphism with cognitive function in acute ischemic stroke patients.